Clozapine-associated Development of Second-onset Obsessive Compulsive Symptoms in Schizophrenia: Impact of Clozapine Serum Levels and Fluvoxamine Add-on - Gahr, M.; Rehbaum, K.; Connemann, B. J. (Pharmacopsychiatry, 2014)
Among antiserotonergic second generation antipsychotics (SGA), particularly treatment with clozapine (CLZ) is associated with the development of second-onset obsessive compulsive symptoms (OCS) in schizophrenia. However, less is known regarding the factors that increase the individual susceptibility for the development of SGA-associated second-onset OCS in schizophrenia. Here we present the case of a 29-year-old female patient with disorganized schizophrenia who exhibited OCS due to fluvoxamine-induced elevation of CLZ serum levels via inhibition of CYP 1A2 und 2C19. The severity of the observed OCS featured an association with CLZ serum levels. The case illustrates the interaction between fluvoxamine add-on and CLZ serum levels on the development of OCS in schizophrenia and emphasizes the need of regular therapeutic drug monitoring.
Keywords: adverse drug reactions; antipsychotic treatment; second generation antipsychotics; side effects; therapeutic drug monitoring